2007
DOI: 10.1183/09031936.00165606
|View full text |Cite
|
Sign up to set email alerts
|

Natural anticoagulants limit lipopolysaccharide-induced pulmonary coagulation but not inflammation

Abstract: Pulmonary coagulopathy and hyperinflammation may contribute to an adverse outcome in sepsis. The present study determines the effects of natural inhibitors of coagulation on bronchoalveolar haemostasis and inflammation in a rat model of endotoxaemia.Male Sprague-Dawley rats were randomised to treatment with normal saline, recombinant human activated protein C (APC), plasma-derived antithrombin (AT), recombinant human tissue factor pathway inhibitor (TFPI), heparin or recombinant tissue plasminogen activator (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 25 publications
6
37
1
Order By: Relevance
“…Activation of coagulation and impairment of fibrinolysis have been found in ALI/acute respiratory distress syndrome as the result of many causes, including sterile inflammation as well as infection. 17,21,[39][40][41] From this point of view, TRALI may be regarded as part of the ALI/acute respiratory distress syndrome and not as a separate entity, as suggested previously. [5][6][7] In line with this, we recently found that TRALI contributes to mortality in critically ill patients, 7 suggesting that prognosis of TRALI is not as favorable as generally considered but rather may parallel ALI as the result of other causes, at least in certain patient populations.…”
Section: Discussionmentioning
confidence: 81%
“…Activation of coagulation and impairment of fibrinolysis have been found in ALI/acute respiratory distress syndrome as the result of many causes, including sterile inflammation as well as infection. 17,21,[39][40][41] From this point of view, TRALI may be regarded as part of the ALI/acute respiratory distress syndrome and not as a separate entity, as suggested previously. [5][6][7] In line with this, we recently found that TRALI contributes to mortality in critically ill patients, 7 suggesting that prognosis of TRALI is not as favorable as generally considered but rather may parallel ALI as the result of other causes, at least in certain patient populations.…”
Section: Discussionmentioning
confidence: 81%
“…antithrombin and the protein C system) and fibrinolytic activity, caused by high levels of plasminogen activator inhibitor-1 and reduced levels of plasminogen activator activity, as described by CHOI and coworkers [24,25] in patients with ventilator-asociated pneumonia and experimental pneumonia in rats.…”
Section: Discussionmentioning
confidence: 99%
“…(12) Previous animal studies specifically targeting pulmonary coagulopathy showed systemic treatment with anticoagulants to attenuate pulmonary coagulopathy with lung injury. (13)(14)(15) However, systemic treatment with anticoagulants, of course, also affected systemic coagulation. In the present study we investigated the effect of locally administered anticoagulants on pulmonary procoagulant and proinflammatory responses to LPS in a rat model of sepsis-induced lung injury.…”
Section: Introductionmentioning
confidence: 98%